2023
DOI: 10.1002/aic.18089
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable improvement of gas–liquid mass transfer by modifying the structure of conventional T‐junction microchannel

Abstract: Enhancing the mass transfer performance just by modifying the channel structure without external energy input is one of the most important topics for microchemical technology development. This work reports the high-performance gas-liquid mass transfer in a novel step T-junction microchannel. The liquid-side mass transfer coefficient in the step T-junction has been significantly improved by one order of magnitude when compared with the conventional T-junction, which is higher up to 60 Â 10 À4 m/s. To our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Increasing the gas flow rates enlarges the gas-interfacial area and reduces the thickness of liquid film (Supplementary Fig. 4 ), thus improving the mass transfer, which is in good agreement with previous studies 44 , 45 , 47 .…”
Section: Resultssupporting
confidence: 92%
“…Increasing the gas flow rates enlarges the gas-interfacial area and reduces the thickness of liquid film (Supplementary Fig. 4 ), thus improving the mass transfer, which is in good agreement with previous studies 44 , 45 , 47 .…”
Section: Resultssupporting
confidence: 92%
“…Due to the advantages of excellent mass transfer performance, 1,2 the emerging gas–liquid microreaction technology enters its period of rapid development, 3–5 and it provides many opportunities for chemical engineers to ensure the safety and high efficiency of the chemical processes, such as oxidation, 6 halogenation, 7 and carbonylation, 8 and so forth. Compared with the inertial force and buoyant force in channels with mill‐meters or centimeters, a lot of studies have revealed the dominance of the interfacial tension and viscous force on the flow behavior with the micro‐scale.…”
Section: Introductionmentioning
confidence: 99%